(untitled) (The Review of Diabetic Studies, 2024)
Achieving health security and universal health coverage (UHC) requires a resilient health system (RHS). Strategies for RHS to enhance UHC and health security, however, are little understood. In order to comprehend methods for constructing RHS toward UHC and health security, this systematic review attempts to synthesize the literature. The final review contained 57 papers in total. Task-shifting policies, results-based health finance policies, and context-based redistribution of health personnel all contributed to the development of RHS. Realizing UHC and health security required strong governmental commitment, multi-sectoral cooperation, and community-based response planning. Conversely, the obstacles to attaining UHC and health security included lack of access, unresponsive, unequal healthcare services, inadequate surveillance, feeble leadership, and income disparities. The obstacles to attaining UHC and health security also included a lack of fundamental healthcare infrastructures, underqualified health workforces, unclear government policy, unclear stakeholder roles, and an unequal distribution of medical facilities and personnel. Conclusions: Achieving UHC and health security requires sophisticated healthcare infrastructures and a sufficient number of healthcare professionals. They are insufficient on their own, though, to safeguard the health system against possible failure. Building RHS toward UHC and health security requires context-specific redistribution of health workers, task shifting, result-based health finance strategies, and integrated and multi-sectoral methods based on primary health care principles.